Integrated biostratigraphy and palaeoenvironmental interpretation of the Upper Cretaceous to Paleocene succession in the northern Moldavidian Domain (Eastern Carpathians, Romania). (September 2017) - Ţabără, Daniel; Slimani, Hamid; Mare, Silvia; Chira, Carmen Mariana
Abstract: This study of the upper Maastrichtian to Danian sedimentary succession from the northern part of the Romanian Eastern Carpathians (Varniţa section) aims to establish an integrated biostratigraphy based on calcareous nannofossils, organic-walled dinoflagellate cysts (dinocysts) and foraminiferal assemblages, and to reconstruct the depositional environments of the interval. The stratigraphic record across the studied section is incomplete, considering that an approximately 16 m thick strata interval from the top of the Maastrichtian to lowermost Danian cannot be analyzed due to a landslide covering the outcrop. The upper Maastrichtian is marked by a succession of biostratigraphic events, such as the First Appearance Datum (FAD) of the nannoplankton taxon Nephrolithus frequens and FAD of the dinocyst species Deflandrea galeata and Disphaerogena carposphaeropsis, and the Last Appearance Datum (LAD) of Isabelidinium cooksoniae in the lower part of the section. These bioevents are followed by the LAD of the Dinogymnium spp. and Palynodinium grallator dinocyst markers in the top of the Maastrichtian deposits analyzed. In terms of foraminiferal biostratigraphy, the upper Maastrichtian Abathomphalus mayaroensis Zone is documented in the lower part of the studied section. Some bioevents, such as the bloom of the calcareous dinoflagellate genus Thoracosphaera and the FAD of the organic-walled dinocysts Damassadinium californicum, Senoniasphaera inornata, Xenicodinium lubricum and X. reticulatum suggest an early Danian age for the middle part of the section. From the Danian deposits in the Varniţa section, we describe a new organic-walled dinocyst species, Pentadinium darmirae sp. nov., which is until now the only species of the Pentadinium genus discovered in the Paleocene. The occurrence of the global Danian dinocyst marker Senoniasphaera inornata in the top of the section, suggests an age not younger than middle Danian (62.6 Ma) for the analyzed deposits. The palynofacies constituents, as well as the agglutinated foraminiferal morphogroups, used to reconstruct the depositional environments, show that the late Maastrichtian sediments were deposited in an outer shelf to distal (bathyal) environment, followed by a marine transgression during the Danian. Highlights: Microfossils of the K–Pg sedimentary succession, Eastern Carpathians, are studied. A new dinoflagellate cyst species was identified. Paleoenvironmental conditions based on palynofacies and microfossils are discussed.